Analysis of Visual Acuity According to the Intensity of Artificial Light - Cristea, Luciana; Bulmaga, Marina; Ungureanu, Loredana; Cazangiu, Diana (Applied Mechanics and Materials, 2014)
Human activity takes place mostly under control from the visual organ. Approximately 80-90 % of the information is perceived through this organ. In these circumstances, an important role has the appropriate lighting, particularly in the labour process as it prevents strain and fatigue, stimulates the activity of the whole body, accelerates nerve functions, positively influences the ability to work and increases work productivity. The subject of this paper is to assess how artificial light affects our eyesight and how we react to visual stress induced by it.